Perencanaan Lanskap Gereja Bet’El di Desa Fatuat Berbasis Partisipasi untuk Meningkatkan Kualitas Ruang Ibadah - Theodora Murni Cintya Tualaka; Imanuel Nuwa Mbake; I Gusti Ngurah Wiras Hardy; Aplimon Jerobisonif; Thomas Kurniawan Dima; Debri Andries Amabi (Institut Pertanian Bogor, 2026)
Church buildings function not only as places of worship but also as sacramental centers that support the spiritual life of their congregations. The church landscape also shapes the spiritual and social experiences of the congregation by serving as a transitional space before and after worship activities. In the context of rural churches, landscape planning often remains unable to optimally support sacred functions, social needs, and outdoor spatial comfort. This community service activity aimed to plan the landscape of Bet’El Church in Fatuat Village as a response to the partner’s problems, particularly the need for a functional worship space that reflects religious values and aligns with local values. The methods included field surveys, spatial needs analysis based on congregational activities, and participatory planning involving the community, village government, traditional elders, and the church development committee. The outputs of this activity consisted of technical drawing documents, a landscape zoning plan, and a cost budget plan. The resulting landscape planning included circulation arrangement, social spaces, reflective spaces, transitional spaces, gate design, and drainage planning. This community service program not only produced a physical site plan but also improved community understanding of the importance of landscape planning as part of the worship experience, local identity strengthening, and the sustainability of church space.